Comparative efficacy of individual renin–angiotensin system inhibitors on major renal outcomes in diabetic kidney disease: a network meta-analysis. Issue 11 (22nd March 2018) - Cai, Juyu; Huang, Xianxi; Zheng, Zhongsheng; Lin, Qing; Peng, Mian; Shen, Daoqian
Abstract: Background: Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are two drug classes with well-documented renal protective effects. However, whether there is any difference among individual drugs remains unknown. In this study, we aimed to compare the efficacy of individual ACEIs/ARBs on major renal outcomes in adults with diabetic kidney disease (DKD). Methods: We conducted a Bayesian-framework network meta-analysis with a random effects model. We searched PubMed, Embase, Scopus, the Cochrane Central Register of Controlled Trials and ClinicalTrials.gov for clinical trials of ACEIs or ARBs as monotherapy compared with other conventional antihypertensive drugs or placebo. Primary outcomes were end-stage renal disease (ESRD) and albuminuria/proteinuria (including change in albuminuria/proteinuria, progression to macroalbuminuria and remission to normoalbuminuria). Secondary outcome was doubling of serum creatinine levels. We also assessed for hyperkalemia, cough and angioedema/edema. International prospective register of systematic reviews (PROSPERO) registration CRD42016036997. Results: A total of 100 studies with data for 22 365 DKD patients, the majority of whom had type 2 diabetes, were included. Individual ACEIs and ARBs at goal doses showed no significant differences in ESRD and doubling of serum creatinine levels. They also shared similar effects on albuminuria/proteinuria reduction and progression or remission of albuminuria. When combining three outcomes of albuminuria/proteinuria as a single endpoint, most ACEIs/ARBs consistently showed favorable antiproteinuric effect, with little difference in the possibility of being the superior treatment for improving albuminuria/proteinuria. Primary outcomes did not change substantially in meta-regressions and sensitivity analyses. Findings were limited by lack of dose equivalence and paucity of data for some outcomes. Conclusions: Based on the available evidence, individual ACEIs and ARBs at goal doses appeared to have no or little differences in their effect on major renal outcomes.